Identification of factors that influence the effectiveness of supplementary feeding for under-five year PEM children in Bogor - . Hartoyo; Dwi Hastuti; Dodik Briawan; Budi Setiawan; Lilik N Yuliati (Media Gizi dan Keluarga, 2001)
The study was intended to determine the impact of supplementary feeding on nutritional status of under-five years old children and to identify the factors that influence the effectiveness of supplementary feeding. The design of the study was follow-up intervention that covered of 211 samples of children suffered from protein-energy malnutrition (PEM) in four selected villages of South Bogor Sub-district. Supplemental food was provided for 90 days during September-November 2000. The results indicate that the average body weight of children has substantially increased, particularly during the first and second months of the intervention. The increase could be attributed to the provision of supplemental food. The increase of Z-score is directly influenced by nutritional status at the beginning of intervention, mother¡¦s participation in the intervention, level of consumption, and duration of illness. Meanwhile, child-care practices, socio-economic status of the family, and child characteristics are among the factors that indirectly affect the increase of Z-score. It is suggested that supplementary feeding program should be simultaneously followed by nutrition and child-care education and health care programs to increase the effectiveness of supplementary feeding program.